Forecast errors and the macroeconomy: a non-linear relationship? - Ulrich Fritsche; Jörg Döpke (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The paper analyses the reasons for departures from strong rationality of German business cycle forecasts based on annual observations from 1963 to 2004. We rely on forecasts from the joint forecast of the so-called "six leading" forecasting institutions in Germany. We test for a non-linear relation between forecast errors and macroeconomic fundamentals and find evidence for such a non-linearity for inflation forecasts. Evidence from probit models further suggests that some macroeconomic fundamentals – especially monetary factors – correlate to large positive or negative forecast growth and inflation forecast errors.
Keywords: E37; E32; C53; C52; 330; forecast error evaluation; non-linearities; business cycles